Exploring the benefits of minimobility in the urban context: The case of central Stockholm - Riggs, William; Shukla, Shivani (Journal of Transport and Land Use, 2021)
Over the past decade, there has been rapid growth in the development and infusion of new and disruptive transportation. Some of the pivotal emergent technologies range from micro-mobility and bikeshare to ridesourcing that is set to utilize automated vehicles. This paper introduces and defines minimobility that falls between a regular ridesourcing/taxi option and micromobility, and also providing critical logistics services during the era of COVID-19. In Central Stockholm the platform has provided a safe and environmentally friendly mode choice that occupies limited space and efficiently serves on the congested city network. We explore potential economic and environmental benefits of minimobility, discussing the advantages and disadvantages of deploying such a service. While we demonstrate a general increase in VMT, consistent with other work showing increased travel from new mobility, due to the electric platform this increase in customer access to mobility results in minimal GHG impacts. This informs how planners and engineers can explore minimobility platforms not only as reduced emissions solutions to urban transit issues but as tools to increase total mobility particularly for the most vulnerable.